Histopathological and Functional Evaluation of Radiation-Induced Sciatic Nerve Damage: Melatonin as Radioprotector - Dheyauldeen Shabeeb; Ahmed Eleojo Musa; Mansoor Keshavarz; Farid Esmaely; Gholamreza Hassanzadeh; Alireza Shirazi; Masoud Najafi (Medicina, 2019)
Background and Objectives: Radiotherapy uses ionizing radiation for cancer treatment. One of the side effects of radiotherapy is peripheral neuropathy. After irradiation, the first stage of neuropathy involves electrophysiological, biochemical and histopathological variations, while the fibrosis of soft tissues surrounding the exposed nerve occurs in the second stage. The present study aimed to examine the radioprotective effects of melatonin against ionizing radiation-induced sciatic nerve damage. Materials and Methods: Sixty male Wistar rats were assigned to four groups: C (Control + Vehicle), M (Melatonin), R (Radiation + Vehicle), MR (Radiation + Melatonin). Their right legs were irradiated with a 30 Gy single dose of gamma rays. Then, 100 mg/kg melatonin was administered to the animals 30 min before irradiation once daily (5 mg/kg) until the day of rats’ sacrifice. Their exposed nerve tissues were assessed using the sciatic functional index (SFI) and histological evaluation. Results: Four, 12 and 20 weeks post irradiation, the SFI results showed that irradiation led to partial loss of motor nerve function after 12 and 20 weeks. Histological evaluation showed the various stages of axonal degeneration and demyelination compared to the C and M groups. Scar-like tissues were detected around the irradiated nerves in the R group at 20 weeks, but were absent in the MR group. The SFI and histological results of the R group showed partial nerve lesion. However, in all cases, treatment with melatonin prevented these effects. Conclusions: Results showed that melatonin has the potential to improve functional and morphological features of exposed sciatic nerves. This could possibly improve the therapeutic window of radiotherapy.